Evaluation of Contact Lens Multipurpose Solutions on Bacterial Biofilm Development. Issue 3 (May 2015) - Artini, Marco; Cellini, Andrea; Scoarughi, Gian Luca; Papa, Rosanna; Tilotta, Marco; Palma, Stefano; Selan, Laura
Abstract : Objectives: No sooner are contact lenses (CLs) inserted into the eyes than lipids, proteins, and glycoproteins rapidly accumulate on their surface, thus favoring the adhesion of commensal bacteria and biofilm formation. Infections may be caused by the proliferation of indigenous flora or other opportunistic pathogens. Our purpose was to evaluate the activity and the capacity of different CL solutions to interfere with the mechanisms of biofilm formation and stability and use of a system to study dynamically biofilm development. Methods: We evaluated the antibiofilm activity of three different multipurpose solutions (MPSs): Regard, Biotrue, and OPTI-FREE PureMoist on four bacterial species ( Serratia marcescens, Pseudomonas aeruginosa, Staphylococcus epidermidis, and Staphylococcus aureus ). Static biofilm assay was first performed to analyze the effect of MPSs. Dynamic assays were performed with the BioFlux system to analyze the effect of the OxyChlorite solution Regard on the biofilm formation. Results: Our studies show that MPSs are able to completely inhibit biofilm formation of Staphylococcus species and of S. marcescens after only 4 hr of incubation. Moreover, a reduction of biofilm formation by Pseudomonas was noted. Best results on P. aeruginosa were obtained with Regard. Regard was also used for dynamic assay, revealing its ability to disaggregate the mature biofilm. Regard completely inhibited biofilm formation by S. epidermidis and slowed down biofilm development by P. aeruginosa . Conclusions: Our findings indicate that the CL solutions tested were all able to reduce biofilm formation. Furthermore, the BioFlux system was proven to be useful for the evaluation of the effectiveness of CL solutions against microbial biofilm formation. Abstract : Supplemental Digital Content is Available in the Text.